PENGARUH PENAMBAHAN JUICE JAMBU BIJI MERAH (Psidium guava L.) TERHADAP RASA DAN AROMA YOGHURT SUSU KAMBING - Giral Pasa; Soegeng Herijanto; Fani Evadewi; Heri Supriyadi (MEDIA PETERNAKAN, 2025)
Abstract.The aim of research entitled "The Effect of Adding Red Guava Juice (Psidium guava L.) on the Taste and Aroma of Goat Milk Yoghurt" was to determine the effect of adding red guava juice (Psidium guava L.) on the taste and aroma of goat's milk yoghurt. This research used goat's milk, red guava and plain yoghurt. The experimental design used was an experimental method with a completely randomized design (CRD) with a unidirectional pattern with four types of treatment, namely P0 (control), P1 (addition of 5% red guava juice), P2 (addition of 10% red guava juice), P3 (addition of 10% red guava juice). addition of 15% red guava juice, each treatment with 5 repetitions. The parameters observed included taste and aroma using 25 semi-trained panelists. The results showed that the addition of red guava juice (Psidium guava L.) had a very significant effect (P<0.01) on the taste and aroma of goat's milk yoghurt. Treatment P3 (15%) is the most popular taste and aroma assessment by panelists because red guava juice produces a quite sour taste and covers the typical aroma (prengus) of goat's milk